Observing The Differences in Constitutional Court Decision About the Legal Age of Marriage - Mia Hadiati; Febriansyah Ramadhan (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
In 2014–2017, there were two tests of the same norms in the Marriage Law, namely the Constitutional Court Decision Number 74 / PUU-XII / 2014 and 22 / PUU-XV / 2017. However, there is a difference in the verdict between one judgment and the next. In Constitutional Court Decision Number 22/PUU-XV/2017, the Constitutional Court changed the previous stance that stated that the age limit norm was constitutional, changing it to unconstitutional, which led to the follow-up of the lawmakers to revise the Marriage Law. This study will compare judges' considerations in the decisions of Constitutional Court Number 74 / PUU-XII / 2014 and Number 22 / PUU-XV / 2017. It will be sought against the Constitutional Court's background changing its stance from one ruling to the next. This research uses normative research methods with a conceptual and philosophical approach to legislation. The results showed that the difference underlying the two rulings was in the excavation of legal sources by judges in their legal considerations.